(untitled) - Crandell, Thomas L. (Boston, 2009)
Human development, 9th ed., continues to provide a well-written, chronological view of lifespan development. It combines up-to-date coverage of research with applications and real-life examples that appeal to nursing and educatuon students, as well as parents. The text includes coverage of social policy, cross-cultural topics, and current health.
Keywords: Developmental psychology,Developmental psychobiology,Tâm lý phát triển,Tâm sinh lý phát triển